Risiko Pendapatan Usahatani Tumpang Sari Cabai Rawit dan Tembakau di Subak Gede Sukawati, Kabupaten Gianyar - CHRISTIE, GABRIELLA BRENDA; DEWI, RATNA KOMALA; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p08, 2022)
Income Risks of Capsicum Frutescens L. and Nicotiana Tabacum Farming in  Subak Gede Sukawati, Gianyar Regency.  Land size, planting distance, capital, maintenance, and weather affect production yields and farmers' incomes. Therefore, farmers must be able to take the right decisions to minimize farming risks. This study aims to determine the risk of production, price, and income of capsicum frutescens L and nicotiana tabacum intercropping farming in Subak Gede Sukawati, Gianyar Regency. Data were analyzed using the calculation of variance, standard deviation, coefficient of variation, and descriptively. Production risk in capsicum frutescens L and nicotiana tabacum intercropping shows the lowest risk with a coefficient of variation of 0.14 when compared to capsicum frutescens L and nicotiana tabacum monoculture. The risk of capsicum frutescens L production is higher (0.34) than nicotiana tabacum (0.30). The price risk in nicotiana tabacum farming, which is 0.12, indicates a higher price risk than the risk in capsicum frutescens L farming (0.02). As for income risk, the lowest risk occurs in capsicum frutescens L and nicotiana tabacum intercropping farming, which is 0.13. This risk is lower when compared to the monoculture of capsicum frutescens L (0.38) and nicotiana tabacum (0.30). The selection of cropping patterns in Subak Gede Sukawati, among others, is based on habits carried out for generations, product selling prices, maximizing income, and production costs.